Impact of the COVID-19 pandemic on the severity and management of acute appendicitis - Poget, Marion; Chautems, Roland; Kohler, Rémy; Diana, Michele; Saadi, Alend (Frontiers in Surgery, 2022)
Background: The literature seems to indicate that the number of appendectomies dropped at the beginning of the Coronavirus disease of 2019 (COVID-19) pandemic while the number of complicated appendicitis increased due to late presentation. In addition, a longer delay before surgical treatment resulted in a higher morbidity. This study aims to compare the number of appendectomies, the severity, and the management of acute appendicitis during the first two pandemic peaks of COVID-19 with those observed during the same seasonal periods in the previous two years in a regional hospital in Switzerland. Methods: We retrospectively reviewed and compared the number of appendectomies, rate of complicated appendicitis, delay to consultation and to surgery, distribution of appendectomies over a 24-hour schedule, postoperative outcomes, and rates of overall complications in 177 patients, that is 66 during the COVID-19 pandemic and 111 before the pandemic. Results: No statistical difference was found in the number of appendectomies, duration of symptoms before consultation, median time to surgery, number of appendectomies performed outside the usual scheduled time for non-urgent surgery, length of postoperative stay, or the rates of overall complications. However, there was a trend in the rate of complicated appendicitis (p = 0.05). Conclusions: In spite of a high incidence rate of COVID-19 in our canton, the impact of COVID-19 on our population did not follow the pattern observed elsewhere. The reasons might be that people would still present to the emergency department due to less strict social distancing measures. Great availability of emergency operating room may also account for the unchanged delay preceding surgical treatment and complication rates.